(untitled) (Konferensiyalar | Conferences, 2024)
The prerequisites for the education of a multicultural personality are laid in preschool age and at the stage of a child’s education in primary school. Concretization of the qualities that form the basis of a multicultural personality is possible from the perspective of an anthropological approach, in the context of consideration of the age and psychological characteristics of children of primary school age.